(untitled) (International Journal of Engineering and Computer Science, 2015)
In today’s world networks plays a vital role in our daily life. The whole world is evolving with networks. The main purpose of this work to provide security in networks, because high-security is required for the network system. It is basically a protecting structure which only desires the encrypted raw traffic information from PHY/MAC layer deprived of beholding into the contents of the interrupted packets. The data is sent from source to destination without being decrypted with help of routing jammers like file appended, data appended and datum modifier. The data which are in the transmission layer is in the form of jammed data in the form of false data. The communication part is taken over by jammer. The jammer works inertly to achieve road traffic investigation based on geometric physiognomies of bagged raw traffic with the help of end to end communication. By doing so, the goal of achieving upright precision in revealing the veiled traffic pattern is obtained.